1998
DOI: 10.1159/000028719
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Tethering: A Common Long-Term Problem after Lipomyelomeningocele Repair

Abstract: The authors reviewed the records of 94 patients who underwent initial repair of a lipomyelomeningocele between 1982 and July 1996 at the Children’s Hospital of Pittsburgh to determine the incidence and time course of symptomatic retethering. In each of these patients, the initial operative goals were to microsurgically debulk as much of the lipoma as possible to allow the conus to move freely within the spinal canal, to divide any tethering arachnoidal adhesions, to close the pia if possible and to reconstitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 14 publications
4
57
0
5
Order By: Relevance
“…As they correctly emphasized, worse results have been reported by the Parisian authors 5,12,15,16 and also by others, 1 but the incidence of spinal cord retethering following lipoma resection has been repeatedly found to be between 10% and 20%. 2,3,4,13 Apart from the cited papers by Pang et al, 10,11 there are also papers by other authors reporting results quite comparable with ours. For instance, Wu et al 14 demonstrated that 84% of their 43 patients maintained stable urodynamic and neurological functions after surgery.…”
Section: Responsesupporting
confidence: 88%
“…As they correctly emphasized, worse results have been reported by the Parisian authors 5,12,15,16 and also by others, 1 but the incidence of spinal cord retethering following lipoma resection has been repeatedly found to be between 10% and 20%. 2,3,4,13 Apart from the cited papers by Pang et al, 10,11 there are also papers by other authors reporting results quite comparable with ours. For instance, Wu et al 14 demonstrated that 84% of their 43 patients maintained stable urodynamic and neurological functions after surgery.…”
Section: Responsesupporting
confidence: 88%
“…7,13,15,19 The pattern of postoperative deterioration compared with preoperative symptoms from the British Columbia Children's Hospital series is shown in Table 2. Of those patients presenting with normal neurological function, without orthopedic or sphincteric dysfunction, 59% continued to experience clinically normal function throughout the last follow-up.…”
Section: Incidence and Timing Of Deterioration Followingmentioning
confidence: 99%
“…Figure 1 provides an approximation of the time to deterioration for nonsurgically treated LMMCs; the curves indicate the deterioration following surgical untethering. 7,15,19 The British Columbia's Children's Hospital, Paris, and Pittsburgh series included all patients and the Chicago series included only those with symptoms prior to untethering. The findings in the more recently published NEM series were not substantially different from reports published earlier.…”
Section: Incidence and Timing Of Deterioration Followingmentioning
confidence: 99%
See 2 more Smart Citations